Classification of Nanomaterial Drug Delivery Systems for Inflammatory Bowel Disease - Wang H; Zhou F; Shen M; Ma R; Yu Q (International Journal of Nanomedicine)
Haichen Wang,1,* Feifei Zhou,2,* Mengdan Shen,1 Ronglin Ma,1 Qiang Yu1 1Department of Gastroenterology, The Affiliated Suzhou Hospital of Nanjing Medical University, Suzhou Municipal Hospital, Gusu School, Nanjing Medical University, Suzhou, Jiangsu, 215002, People’s Republic of China; 2Department of Gastroenterology, Suzhou City Wuzhong District Chengnan Street Community Health Service Center, Suzhou, Jiangsu, 215002, People’s Republic of China*These authors contributed equally to this workCorrespondence: Qiang Yu; Ronglin Ma, Email yuqiang0102sz@163.com; maronglin573@163.comAbstract: Inflammatory bowel disease (IBD), including Crohn’s disease and ulcerative colitis, primarily arises from defects in the colonic barrier, imbalances of the gut microbiota, and immune response issues. These complex causes make it difficult to achieve a complete cure. Patients with IBD frequently experience recurrent abdominal pain and bloody diarrhea, while severe cases may result in intestinal obstruction, perforation, and cancer. Lifelong maintenance therapy may thus be needed to manage these symptoms; however, traditional IBD drugs, such as 5-aminosalicylic acid, glucocorticoids, immunosuppressants, and biological agents, are often associated with problems including poor solubility, instability, and ineffective targeting, as well as causing serious side effects in non-target tissues. Nanomaterial drug delivery systems (NDDS) have recently shown great promise in optimizing drug distribution, solubility through biocompatible coatings, enhancing bioavailability via PEGylation and reducing side effects. These formulations can enhance a drug’s pharmacokinetics by modifying its properties, improve its ability to cross barriers, and boost bioavailability. In addition, NDDS can enable targeted delivery, increase local drug concentrations, improve efficacy, and reduce side effects, as well as protecting active drug molecules from immune recognition and protease degradation. The clinical use of these systems for treating IBD, however, requires further research. This review summarizes the classification of NDDS for IBD, and concludes that, despite ongoing challenges, NDDS may represent an effective treatment approach for IBD. In summary, NDDS enhance the targeted delivery of therapeutic agents to specific cells or tissues, thereby improving drug bioavailability and therapeutic efficacy. These systems effectively surmount biological barriers, facilitating efficient drug delivery to targeted sites, which is crucial for attaining optimal therapeutic outcomes. This review contributes to a deeper understanding of how the physicochemical properties of NDDS influence pharmacological behavior in vivo and can expedite their clinical translation.Keywords: inflammatory bowel disease, nanomaterials, drug delivery, nano-delivery systems, nanomedicine applications